Does Motivation and Trust Important for Tourists’ Loyalties? A Quantitative Perspective from Golf Tourism in Bali of Indonesia - Kuhn, Panudiana; Bendesa, Komang Gde; Wiranatha, Agung Suryawan; Oka Suryawardani, I Gusti Ayu (E-Journal of Tourism; Volume 6 Number 1 (March 2019), 2019)
Golf is one of several sport tourist attractions that are increasingly demanding by domestic and foreign tourists during their visit to Bali. Unlike the others type of tourist attractions, golf tourism could be classified as a quality attraction. Tourists who play golf spend more money than other sport activities. Refers to this fact, golf tourism could be an alternative to realizing the establishment of quality tourism in Bali. This work aims to study the significance of the determinants of tourists' satisfaction as well as their loyalty in visiting Bali as a destination that offers golf attractions. Intrinsic motivation and extrinsic motivation from golfers are positioned as the antecedent of the level of satisfaction with their trust to the golf providers acts as the mediation of the causal relationship occured. Using 5-scale Likert questionnaire, the opinions of 113 foreign tourists who played golf in Bali were used to examine the structural equation models that were built. The results of the analysis show that both types of motivation have positive influences on tourist trust in golf operators, and through the trust mediation, these motivations positively influence the level of tourist loyalties. The results of the analysis also showed that tourists’ trust to the golf operators had a significant effect on tourist loyalty. The main findings of this research conclude the vital role of tourists’ trust to the golf operators in Bali in increasing their loyalty to play golf while visiting Bali. Keywords : golf, trust, satisfaction, loyalties, motivation, SEM.